Bio-functionalized silk hydrogel microfluidic systems. (July 2016) - Zhao, Siwei; Chen, Ying; Partlow, Benjamin P.; Golding, Anne S.; Tseng, Peter; Coburn, Jeannine; Applegate, Matthew B.; Moreau, Jodie E.; Omenetto, Fiorenzo G.; Kaplan, David L.
Abstract: Bio-functionalized microfluidic systems were developed based on a silk protein hydrogel elastomeric materials. A facile multilayer fabrication method using gelatin sacrificial molding and layer-by-layer assembly was implemented to construct interconnected, three dimensional (3D) microchannel networks in silk hydrogels at 100 μm minimum feature resolution. Mechanically activated valves were implemented to demonstrate pneumatic control of microflow. The silk hydrogel microfluidics exhibit controllable mechanical properties, long-term stability in various environmental conditions, tunable in vitro and in vivo degradability in addition to optical transparency, providing unique features for cell/tissue-related applications than conventional polydimethylsiloxane (PDMS) and existing hydrogel-based microfluidic options. As demonstrated in the work here, the all aqueous-based fabrication process at ambient conditions enabled the incorporation of active biological substances in the bulk phase of these new silk microfluidic systems during device fabrication, including enzymes and living cells, which are able to interact with the fluid flow in the microchannels. These silk hydrogel-based microfluidic systems offer new opportunities in engineering active diagnostic devices, tissues and organs that could be integrated in vivo, and for on-chip cell sensing systems.